Thiosemicarbazone Complexes of Uranium(IV). Issue 12 (19th February 2021) - Grödler, Dennis; Haseloer, Alexander; Tobeck, Christian; Bulut, Yusuf; Neudörfl, Jörg M.; Mathur, Sanjay; Ruschewitz, Uwe; Klein, Axel; Wickleder, Mathias S.; Zegke, Markus
Abstract: The first homoleptic thiosemicarbazone complexes of uranium were isolated by reacting uranium tetrachloride in a salt metathesis or acid‐base reaction with four equivalents of Na(BzTSC) or H(BzTSC) (BzTSC=benzylthiosemicarbazone), carrying a non‐methylated (L1 ), monomethylated (L2 ) or dimethylated (L3 ) terminal amino group, in moderate yields. [U(BzTSCNH2 )4 ] (1 ), [U(BzTSCNH(CH3 ))4 ] (2 ) and [U(BzTSCN(CH3 )2 )4 ] (3 ) show a remarkable stability towards air, with oxidation potentials in THF between +0.43 and +0.53 V and reduction potentials between −2.53 and −2.67 V vs. ferrocene/ferrocenium. The simple methylation of the terminal amino group of the ligand allows for controlled changes in the coordination environments of the complexes. Thermogravimetric analyses indicate that the complexes are stable up to 155 °C. Abstract : Uranium changes color. Herein we present the first uranium(IV) thiosemicarbazone complexes. Their coordination is tunable depending on the N‐methylation of the ligand. This results in the inclusion and exclusion of THF solvent, leading to a change in color from yellow to red, but the spectroelectrochemical properties remain the same. The complexes are insensitive to oxidation or reduction within a potential range from +0.4 to −2.50 V in THF.